Stop the Loop Board Game: Microbiologist Version - Noor Jannah Yob (Malaysia Journal of Invention and Innovation, 2024)
Experiences in the laboratory can stimulate interest in science. Experiments are one of the hands-on activities used to develop knowledge and understanding of scientific concepts. Microbiology is a subject that involves the study of complex microorganisms and intricate protocols. Early instruction can help students prepare for all the opportunities that may arise when experimenting in the lab. "Stop the Loop" is a board game that integrates the concept of microbiology and learning through play into an educational game. In this game, the player must face the challenge of stopping the loop and, by chance, finishing the game first and winning. Students experience the challenges that can occur during the experiment and the actions that can be a solution or a problem for the given situation. Through this game, students learn through play while learning the basic concepts of microbiology using visual mnemonics. The situation can help students imagine a real situation that could happen and think about the situation to minimize the error. This game not only increases motivation and participation but can also promote critical thinking and problem solving. This game concept can also be used for different kinds of experiments in many study subjects as a teaching tool for lecturers or teachers in colleges. It could also be marketed as a commercial family game that can be experienced and played by all ages.